EFFECT OF DIFFERENT ESTRUS SYNCHRONIZATION ON SERUM E2, P4, FSH AND LH DURING DIFFERENT ESTRUS PERIODS AND PREGNANCY IN EWES - Al-Marzani, E. A. H.; Barwary, M. S. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2022)
This research was designed to know the effect of different estrus synchronization protocols on Serum E, P, FSH, and LH during different estrus periods and pregnancy in Karadi and Arabi ewes. The study was carried out by using 30 ewes for each breed at 2-4 years. Ewes from each breed were equally and randomly distributed into three groups. The first group was treated with vaginal sponges saturated with (60 mg) of Medroxy progesterone acetate within a period of (14) fourteen days (T1). The second group was administrated with the MAP injected with a dose of 300 IU / head of the hCG (T2). The third group was treated with MAP treatment, and injected at a dose of 75 µg /head of GnRH (T3). The results of this analysis showed a significant increase in the estrogen concentration in the different reproductive stages; the significant level of estrogen in the estrus phase (60.96) pg/ml. The concentration of progesterone differed significantly in the different reproductive stages, with the highest concentration in the pregnancy period (16.33) pg/ml. In comparison, the FSH concentration differed significantly in the different reproductive stages with the highest concentration in the estrus period(3.243) mIU/ml. the highest significant level of serum LH is in the estrus period (5.230) mIU/ml. Thus, the study is concluded that hormones and phases may be effective in inducing follicular growth and ovulation and finally may increase pregnancy rate and production .